2017
DOI: 10.1016/j.scitotenv.2017.06.173
|View full text |Cite
|
Sign up to set email alerts
|

Using ecosystem engineers as tools in habitat restoration and rewilding: beaver and wetlands

Abstract: Potential for habitat restoration is increasingly used as an argument for reintroducing ecosystem engineers. Beaver have well known effects on hydromorphology through dam construction, but their scope to restore wetland biodiversity in areas degraded by agriculture is largely inferred. Our study presents the first formal monitoring of a planned beaver-assisted restoration, focussing on changes in vegetation over 12years within an agriculturally-degraded fen following beaver release, based on repeated sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 57 publications
2
88
0
2
Order By: Relevance
“…Recently, it has been suggested that using ecosystem engineers, such as beaver, to restore ecosystems may lessen the need for direct human intervention (Byers et al., ; Law et al., ; Van Klink & Wallisdevries, ). Our results strengthen the idea that beaver activity can be an important conservation tool by contributing to diversity in areas where they are present.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that using ecosystem engineers, such as beaver, to restore ecosystems may lessen the need for direct human intervention (Byers et al., ; Law et al., ; Van Klink & Wallisdevries, ). Our results strengthen the idea that beaver activity can be an important conservation tool by contributing to diversity in areas where they are present.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the existing body of research showing that wetlands, in the broad sense, act as valuable sediment and nutrient stores (Johnston, 1991), particularly in contrast to anthropogenic degraded landscapes (Nahlik and Fennessy, 2016). Furthermore, results indicate that beaver engineered wetlands are exemplars of such valuable wetlands and can successfully exist or be created within intensively managed European agricultural landscapes (Law et al ., 2017; Puttock et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Dam and pond features can alter hydrological regimes, both locally and downstream (Polvi and Wohl, 2012; Burchsted and Daniels, 2014). The resulting increased structural heterogeneity of the environment (Rolauffs et al ., 2001) also creates a diverse range of habitats (Rosell et al ., 2005) with an increasingly recognised potential as a habitat restoration tool (Law et al ., 2017). In addition to increasing biodiversity (Law et al ., 2017), it has been suggested that, due to their engineering activity, beavers could play a role in the management of river catchments (Puttock et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…; Stringer & Gaywood ; Law et al. ). The restoration of pre‐European landscapes and species assemblages in Australia is in most cases unachievable due to extinctions and the difficulties of removing invasive species.…”
Section: Restoring Processes Rather Than Historic Statesmentioning
confidence: 99%